Impact of the Three Gorges Dam on sediment deposition and erosion in the middle Yangtze River: a case study of the Shashi Reach - Wei Zhang; Jing Yuan; Jianqiao Han; Chengtao Huang; Ming Li (Hydrology Research, 2016)
Channel morphology in an alluvial river usually varies due to the altered flow and sediment regime from upstream damming. This paper reports an evaluation of the dynamical changes of sedimentation and erosion in the middle and lower reaches of the Yangtze River after operation of the Three Gorges Dam (TGD). Here, we present the results from a case study of the Shashi Reach in the middle Yangtze River, which is the first sandy-bed and meandering reach downstream of TGD. Databases were constructed using a digital elevation model of channel topography based on the 1:10,000 topographic maps from the 1980s to 2012 and hydrological records from 1956 to 2013. Results indicate that the erosion in the Shashi Reach was mainly confined to the deeper channel and that it has increased since the construction of the TGD. No significant changes were observed above the bank-full level, resulting in the decrease of the width-to-depth ratio. These changes may be principally caused by variations of the seasonal distribution of flow and sediment due to the operation of the dam. In addition, results show that the cross-sectional shape change of the channel is related to the relative erodibility of the channel bed and bank material.